Trajectory exponential tracking control of unmanned surface ships with external disturbance and system uncertainties. (July 2018) - Qu, Yaohong; Xiao, Bing; Fu, Zhenzhou; Yuan, Dongli
Abstract: Any unmanned surface ship is subject to system uncertainty, unknown parameters, and external disturbance induced by the wind, the wave loads, and the ocean currents. They may deteriorate ship's control accuracy. This paper aims to solve the trajectory tracking control problem of unmanned surface ships with disturbance and system uncertainty accommodated simultaneously. An estimator-based backstepping controller is presented with an estimator designed to provide a precise estimation of the disturbance and uncertainties. The proposed controller ensures the closed-loop tracking system to be globally exponentially stable. The trajectory tracking error and the estimation error of disturbance and uncertainties are globally exponentially stable. The key feature of the developed control scheme is that it is more robust to disturbances and system uncertainties. Simulation results are further presented to validate the effectiveness of the approach. Highlights: In this paper, an estimator-based backstepping controller is presented for unmanned surface ships with external disturbances and system uncertainties. A globally exponentially tracking controller is presented for unmanned surface ships with disturbances and uncertainties. The key feature of the proposed control approach is that it is more robust to external disturbance and system uncertainties.